Dari Piksel ke Paragraf: Pemetaan Kesalahan Penulisan Kalimat Efektif dalam Teks Berita Siswa XI DKV - Salsabila Khoerunnisa; Lalita Melasarianti; Vera Krisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the linguistic competence gap observed in vocational high school (SMK) students majoring in Visual Communication Design (DKV), where dominant visual communication skills are often not matched by adequate verbal-written proficiency. The core issue addressed is the low mastery of effective sentence rules in composing news texts, which demand high objectivity and precise information. This study aims to identify, analyze, and comprehensively map the forms of effective sentence writing errors in news texts produced by eleventh-grade DKV students at SMK Kesatrian Purwokerto. Using a qualitative descriptive approach, the study identifies linguistic lapses based on the framework of Alwi et al. (2017). Data were collected through a news-writing performance test. The results reveal a total of 430 errors classified into five major categories. The most dominant error is "Kecermatan" (Precision, involving Spelling & Capitalization) with 182 findings (42.3%), categorized as "Very High." This is followed by "Kesepadanan Struktur" (Structural Balance) with 98 findings (22.8%) and "Kepaduan" (Coherence) with 76 findings (17.7%), both categorized as "High." Additionally, "Kehematan Kata" (Economy of Words) contributed 45 findings (10.5%) in the "Moderate" category, while "Kelogisan" (Logic) was the least frequent with 29 findings (6.7%). These findings confirm that the "visual thinker" characteristic of DKV students leads them to overlook basic mechanical and structural linguistic precision. This mapping serves as a crucial diagnostic tool for educators to design targeted literacy interventions that bridge the gap between visual creativity and formal written communication requirements in the professional creative industry.